Biological activities of selected plants and detection of bioactive compounds from Ardisia elliptica using UHPLC-Q-Exactive Orbitrap mass spectrometry - Wong, Pei Lou; Fauzi, Nurul Azila; Mohamed Yunus, Siti Norhamimah; Abdul Hamid, Nur Ashikin; Abd Ghafar, Siti Zulaikha; Azizan, Awanis; Zolkeflee, Nur Khaleeda Zulaikha; Abas, Faridah (Multidisciplinary Digital Publishing Institute, 2020)
Plants and plant-based products have been used for a long time for medicinal purposes. This study aimed to determine the antioxidant and anti-α-glucosidase activities of eight selected underutilized plants in Malaysia: Leucaena leucocephala, Muntingia calabura, Spondias dulcis, Annona squamosa, Ardisia elliptica, Cynometra cauliflora, Ficus auriculata, and Averrhoa bilimbi. This study showed that the 70% ethanolic extract of all plants exhibited total phenolic content (TPC) ranging from 51 to 344 mg gallic acid equivalent (GAE)/g dry weight. A. elliptica showed strong 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) scavenging activities, with half maximal inhibitory concentration (IC50) values of 2.17 and 49.43 μg/mL, respectively. Most of the tested plant extracts showed higher inhibition of α-glucosidase enzyme activity than the standard, quercetin, particularly A. elliptica, F. auriculata, and M. calabura extracts with IC50 values of 0.29, 0.36, and 0.51 μg/mL, respectively. A total of 62 metabolites including flavonoids, triterpenoids, benzoquinones, and fatty acids were tentatively identified in the most active plant, i.e., A. elliptica leaf extract, by using ultra-high-performance liquid chromatography (UHPLC)–electrospray ionization (ESI) Orbitrap MS. This study suggests a potential natural source of antioxidant and α-glucosidase inhibitors from A. elliptica.